Export and Import Price Index Manual : Theory and Practice. (Manuals and Guides, 2009)
A joint production by six international organizations, this manual explores the conceptual and theoretical issues that national statistical offices should consider in the daily compilation of export and import price indices. Intended for use by both developed and developing countries, it replaces guidance from the United Nations that is now more than a quarter-century old and thus badly outdated. The chapters cover many topics; they elaborate on the different practices currently in use, propose alternatives whenever possible, and discuss the advantages and disadvantages of each alternative. Given its comprehensive nature, the manual is expected to satisfy the needs of many users in addition to national statistical offices and international organizations, particularly businesses, policymakers, and researchers.